(untitled) (Bulletin of criminological association of Ukraine, 2025)
It has been emphasized that it is impossible to imagine criminal proceedings outside the process of proof and vice versa, because the indicated types of activity are interconnected. It has been emphasized that the criminal process is dynamic, undergoes changes taking into account the development of society, the legal system, etc., and therefore individual elements (institutions) of criminal procedural law evolve, which is reflected in scientific theories. It has been found that the formation and development of scientific thought about the essence, content and significance of means of proof in criminal proceedings was carried out under the influence of many factors and directly depend on the established approaches not only in the science of criminal procedure, but also in evidentiary law. It has been emphasized that the direct influence on the genesis of scientific thought about means of proof in criminal proceedings is exerted by the constant updating of criminal procedural legislation taking into account social needs, for example, against the background of the development of a democratic and legal state, the implementation of international legal standards in the domestic criminal process, the adaptation of the procedure for conducting criminal proceedings to the conditions of martial law, etc. It has been established that the genesis of scientific thought about means of proof in criminal proceedings is relevant to the formation and development of scientific approaches to the definition of the theory of evidence and criminal procedural proof. It has been stated that the formation of scientific thought about means of proof in criminal proceedings falls on the first half of the twentieth century, when means of proof were considered through the prism of the characteristics of the subject of the theory of evidence and the process of proof. It has been noted that the development of the scientific idea about means of proof in criminal proceedings correlates with the historical periods of the development of the criminal process in general and the doctrine of evidence and proof in criminal proceedings in particular. It has been established that with changes in scientific approaches to the definition of evidence in criminal proceedings, scientific positions on the interpretation of means of evidence have also changed: from recognizing evidence as the only means of proof to including it in the system of means of proof along with evidence of procedural actions, forensic means of collecting evidence, logical techniques, etc.